Asuhan Kebidanan Ibu Hamil, Bersalin, Nifas Dan Bayi Baru Lahir Normal Pada Ny “J” Dengan G3P1A1 - Sainah (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to analyze in depth the pattern of Midwifery Care for Pregnant, Maternity, Postpartum and Normal Newborns in Mrs.